Phytochemical antimicrobial and cytotoxicity screening of Aaptos sp. and Xestospongia testudinaria sponges from Panay Island, Philippines - Ereje, Reymark C.
The marine sponges Xestospongia testudinaria and Aaptos sp. were extracted using hexane, (8:2) DCM:MeOH and 100% methanol solvents. The antimicrobial and cytotoxic property of each extract was assessed using cell-based assay. The anti-proliferative assay using CHO-AA8, HCT-116 and MCF-7 cell lines showed that the high dose DCM:MeOH extract of the Aaptos sponge is highly cytotoxic to HCT-116 having 23.96±4.07% cell viability. The high dose DCM:MeOH extract of the Xestospongia sponge exhibited cytotoxicity to breast cancer cells with 48.01±1.57% viability, while the positive control, Taxol has 78.46±7.37% viability. The sponge extracts that were tested against the Staphylococcus aureus, Pseudomonas aeruginosa and Klebsiella pneumoniae pathogenic bacteria showed low inhibitory activities in both high and low doses. The data obtained showed that the bioactivity of the sponges is dependent on the extraction solvents and the concentration of the extracts. Statistical analysis of the anti-proliferative assay showed significant difference among cell lines and dosage across specific extracts.